FOREIGN EXPERIENCE AND NATIONAL PRACTICE IN PROTECTING PRIVATE PROPERTY (Scientific journal of the Fergana State University, 2026)
The article presents the issue of the formation of private property rights and its legal foundations during the еars of independence of the Republic of Uzbekistan. In particular, cases related to the emergence of citizens’ rights private property, methods and forms of their protection, as well as their abolition were analyzed. As a result, certain conclusions were drawn.